2019
DOI: 10.1029/2019gl083593
|View full text |Cite
|
Sign up to set email alerts
|

Observational Evidence for Throat Aurora Being Associated With Magnetopause Reconnection

Abstract: Throat auroras have been suggested to be related to indentations on the subsolar magnetopause. However, the indentation generation process and the resulting ionospheric responses have remained unknown. An EISCAT Svalbard Radar experiment was designed to run with all‐sky cameras, which enabled us for the first time to observe the temporal and spatial evolution of flow reversals, Joule heating, and ion upflows associated with throat aurora. The high‐resolution data enabled us to discriminate that the flow bursts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
(75 reference statements)
1
21
0
1
Order By: Relevance
“…In this study, we identified geomagnetic responses associated with occurrence of throat aurora. Because the observational results can be explained well by integrating the physical models of FTE (Southwood, 1987) and throat aurora model along with observations (Han, 2019;Han et al, 2019), we argue that the results provide further evidence for throat aurora being associated with magnetopause reconnection. The results are also essential to fully understand the processes associated with throat aurora.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…In this study, we identified geomagnetic responses associated with occurrence of throat aurora. Because the observational results can be explained well by integrating the physical models of FTE (Southwood, 1987) and throat aurora model along with observations (Han, 2019;Han et al, 2019), we argue that the results provide further evidence for throat aurora being associated with magnetopause reconnection. The results are also essential to fully understand the processes associated with throat aurora.…”
Section: Resultssupporting
confidence: 54%
“…They also observed the magnetic field variations representing upward/downward FACs in association with throat aurora occurrence. Apart from this above work, mesoscale ionospheric twin flow cells are observed when the ESR swept over throat aurora (Figure 3 from Han et al, 2019). This flow patterns were consistent with the geometry of a model of flux FTE (Southwood, 1987) which provides strong evidence for throat aurora being associated with magnetopause reconnection events.…”
Section: Predictions Of the Modelsmentioning
confidence: 86%
See 1 more Smart Citation
“…First, we stress that throat aurora refers to a particular north‐south aligned discrete auroral form that is extending from the equatorward edge of the discrete auroral oval but is not intensification of an auroral structure that is inside the original aurora oval. Throat aurora has been suggested to correspond to a magnetopause indentation that is caused by magnetopause reconnection (Han et al, 2019). We found that all the auroras shown in Kim et al (2017), Kozyreva et al (2019), and Mende et al (2001) have clear throat aurora features.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The detailed properties of throat aurora are of great significance in investigating how these magnetopause indentations are generated, but they have not been fully understood. Up to the present, it has been revealed that (1) throat auroras are caused by precipitation of magnetosheath particles that are on the open filed lines (Han et al, 2016), (2) throat auroras are often observed to appear from a background of diffuse aurora that is on the closed field lines (Han et al, 2015, 2016), (3) occurrence of throat aurora shows little dependence on the interplanetary magnetic field (IMF) Bz component but shows clear dependence on the IMF cone angle (Han et al, 2017), (4) throat auroras correspond to magnetopause indentations (Han et al, 2016, 2018) and the depth of the magnetopause indentation can be >3.0 Re (Earth Radius) as inferred from the throat auroras observed on the ground (Han et al, 2017), and (5) throat auroras show clear reconnection signatures in the EISCAT radar observations (Han et al, 2019). Based on the above observations, Han (2019) suggested that throat auroras are likely caused by a particular magnetopause reconnection that can deeply develop inward the magnetosphere at a much localized sector.…”
Section: Introductionmentioning
confidence: 98%